The Effectiveness of Indonesian Learning Transformation through a Collaborative Approach in Writing Procedural Texts in Grade VII MTs Students - Rozi, Yahya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effectiveness of collaborative methods in increasing the creativity of grade VII students of MTs Hasyim Asy'ari Kedungmegarih in writing procedural texts. Adopting a descriptive qualitative approach with a case study strategy, data was collected through participatory observation, in-depth interviews, and analysis of student assignment documentation. The results of the study showed that the collaborative method was proven to be successful in increasing students' creativity, indicated by a significant increase in the activeness of discussion, divergent thinking skills, and effective collaboration between group members when drafting procedural texts. A clear division of roles in groups helps optimize the individual potential of students. However, challenges such as disparities in participation and group time management remain of note. Fundamentally, these findings reinforce the urgency of transitioning the learning paradigm from teacher-centered to student-centered, encouraging the exploration of original ideas, developing 21st century skills, and realizing more contextual and meaningful Indonesian learning.